BUSINESS PLAN FOR MOTORCYCLE BODY AND WHEEL PRESS WORKSHOP: MARKET ANALYSIS, OPERATIONAL STRATEGY, AND FINANCIAL FEASIBILITY - Andika Hendriansyah; Muji Setiyo (Journal of Business And Entrepreneurship, 2026)
This study presents a comprehensive business plan for Andika Tech, a specialized body and wheel press workshop. The plan is based on market analysis, customer needs, operational strategies, and financial feasibility to assess the potential sustainability and profitability of the business. Key market opportunities arise from the increasing number of motor vehicles, high accident rates, and the limited availability of specialized workshops. Andika Tech differentiates itself by utilizing precision press technology without heating or hammering, supported by trained owners as technicians, comfortable facilities, and pick-up and delivery services. Marketing strategies leveraging social media aim to enhance customer awareness and expand market reach. Financial analysis indicates positive outcomes across pessimistic, moderate, and optimistic scenarios, with Net Present Value (NPV) ranging from IDR 191,619,000 to IDR 646,578,000, Internal Rate of Return (IRR) from 5% to 13% per month, and Payback Period (PP) from 8 to 15 months. The business is not only financially viable but also contributes socially by creating job opportunities, improving local technician skills, and promoting efficient and affordable vehicle repair services.